Development Trends Of The New Uzbekistan (Eurasian Journal of Engineering and Technology, 2026)
The article presents a comprehensive analysis of the position of the Republic of Uzbekistan in international rankings and indices in recent years. The importance of ratings as an objective reflection of reforms in Uzbekistan in the international arena is emphasized, and the positive dynamics achieved are noted and areas requiring serious attention are clearly identified The country's role in enhancing its international prestige is assessed..